2008
DOI: 10.1177/0731684407081769
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Sorption and Tensile Response of Pultruded E-Glass/Vinylester Composites Subjected to Hygrothermal Exposure and Sustained Strain

Abstract: The aim of the present research is to provide insights into the sorption behavior and degradation mechanisms of a unidirectional pultruded E-glass/vinylester composite subjected to synergistic hygrothermal exposure and sustained bending strain for exposure times of up to 2 years. Composite specimens were found to follow a Langmuir-type diffusion behavior in all environments, with departure from that behavior attributed either to material leaching-out, chemical breakdown, interfacial debonding, or central delam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 27 publications
(49 reference statements)
1
21
0
3
Order By: Relevance
“…In addition to the common susceptibility of resins to ageing, glass fibres (unlike carbon fibres) may also degrade in the presence of moisture with prolonged exposure. As a result, while the initial reduction in strength is believed to be a consequence of degrading resin and fibre/resin interface [35], its further reduction after 840 days can also be attributed to damaged glass fibres [36].…”
Section: Gfrpmentioning
confidence: 99%
“…In addition to the common susceptibility of resins to ageing, glass fibres (unlike carbon fibres) may also degrade in the presence of moisture with prolonged exposure. As a result, while the initial reduction in strength is believed to be a consequence of degrading resin and fibre/resin interface [35], its further reduction after 840 days can also be attributed to damaged glass fibres [36].…”
Section: Gfrpmentioning
confidence: 99%
“…For example, Helbling and Karbhari [15] investigated the degradation mechanisms of a unidirectional pultruded E-glass/vinylester composite subjected to synergistic hygrothermal exposure and sustained flexural strain for different exposure duration up to two years. Study results indicated that the hygrothermal behavior of the pultruded composite specimens evaluated followed a Langmuir-type diffusion behavior in different exposure environments.…”
Section: Introductionmentioning
confidence: 99%
“…When a sustained loading was applied simultaneously, the creep deformation increased the molecular spacing which makes water molecules and NaCl molecules more easily invaded adhesive, thus causing greater deterioration of the reliability and durability of the structural elements [19]. Helbling et al [20,21] reported that sustained bending strain had no influence on moisture uptake, but could cause severe fiber/matrix interfacial debonding, in addition to fiber pitting and cracking.…”
Section: Introductionmentioning
confidence: 99%